An eclipsing-binary distance to the Large Magellanic Cloud accurate to two per cent - Pietrzyński, G.; Graczyk, D.; Gieren, W.; Thompson, I. B.; Pilecki, B.; Udalski, A.; Soszyński, I.; Kozłowski, S.; Konorski, P.; Suchomska, K.; Bono, G.; Moroni, P. G. Prada; et al. (Nature (London), 2013)
Observations of eight long-period, late-type eclipsing-binary systems composed of cool, giant stars are used to determine a distance to the Large Magellanic Cloud accurate to 2.2 per cent, providing a base for a determination of the Hubble constant to an accuracy of 3 per cent. Accurate distance to our nearest-neighbour galaxy The physical properties of stars in eclipsing binary systems can be accurately determined thanks to the intimate interactions between the two bodies, and by monitoring the fluctuating light from such systems it is possible to obtain accurate extragalactic distance measurement. This technique has now been used to determine the most accurate distance estimate yet for the Large Magellanic Cloud (LMC), our nearest-neighbour galaxy. The data from eight long-period, late-type eclipsing systems particularly suitable for this calibration technique suggest that the LMC is around 49.97 kiloparsecs from us, to an accuracy of 2.2%. The distance to the LMC is a key element in determining the Hubble constant, an important measure of the rate of expansion of the Universe. In the era of precision cosmology, it is essential to determine the Hubble constant to an accuracy of three per cent or better 1 , 2 . At present, its uncertainty is dominated by the uncertainty in the distance to the Large Magellanic Cloud (LMC), which, being our second-closest galaxy, serves as the best anchor point for the cosmic distance scale 2 , 3 . Observations of eclipsing binaries offer a unique opportunity to measure stellar parameters and distances precisely and accurately 4 , 5 . The eclipsing-binary method was previously applied to the LMC 6 , 7 , but the accuracy of the distance results was lessened by the need to model the bright, early-type systems used in those studies. Here we report determinations of the distances to eight long-period, late-type eclipsing systems in the LMC, composed of cool, giant stars. For these systems, we can accurately measure both the linear and the angular sizes of their components and avoid the most important problems related to the hot, early-type systems. The LMC distance that we derive from these systems (49.97 ± 0.19 (statistical) ± 1.11 (systematic) kiloparsecs) is accurate to 2.2 per cent and provides a firm base for a 3-per-cent determination of the Hubble constant, with prospects for improvement to 2 per cent in the future.